Relationship between urinary track infection screening tests and urine culture results in patients with suspect urinary track infection - Indriati, Elli; Silviani, Yusianti (Journal of Indonesian Medical Laboratory and Science, 2024)
Background: Urinary tract infection (UTI) is a common disease found in the world. Gold standard for the diagnosis of UTI is urine culture, but this examination has the disadvantage of taking longer results. As a screening test, urine dipstick and urine flowcytometry provide more rapid diagnosis of UTI. Objectives: The purpose of this study was to determine the relationship between the results of the dipstick test and UF4000 with urine culture.  Materials and Methods: This study used an analytic observational method with a cross sectional approach, with accidental sampling. The samples obtained was 38 samples from patients at the Clinical Laboratory of Prodia Diponegoro and Prodia SDP. Results: The results showed that there was 84.2% concordance between leukocyte esterase results and culture results, and 31.6% concordance between nitrite results and culture results, 97.4 5% concordance between urine flowcytometry results and urine culture results. Conclusions: Based on the Chi square statistical, it was concluded that there were relationship between Urine culture and leukocyte esterase (p-value 0.000), nitrite (p-value 0.004, urine flowcytometri (p-value 0.000). Both of these screening tests can be used to help diagnose UTI, but the gold standard for UTI still uses urine culture result.